Pesantren dan Moderasi Beragama; Peran Kiai dalam Membentuk Sikap Moderasi Beragama Mahasantri - Abdullah, Abdullah; Muawaroh, Mundiro Lailatul; Ismail, Moh. (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
Rejecting extremism in religion is the key to balance, for the maintenance of civilization and the creation of peace. Therefore, religious moderation is the key to maintaining tolerance and harmony, both at the local, national and global levels. In this way, each religious community can respect each other, accept differences, and live together in peace and harmony. This research was conducted because the spread of extreme and intolerant ideas is not only aimed at the general public, but also among students and Islamic boarding school students. This research, which was conducted at Ma'had Aly Nurul Cholil Bangkalan, used qualitative-descriptive methods. The research results show that the role of Ma'had Aly Nurul Cholil Bangkalan is very important in instilling and forming an attitude of religious moderation. This institution is a central forum for strengthening faith, developing Islamic knowledge and traditions, pious deeds, and noble morals for mahasantri. Concrete steps were taken by Ma'had Aly Nurul Cholil in forming a religious moderation attitude among mahasantri by providing in-depth religious knowledge, being selective in teaching staff, and being accommodating to local culture. In this case, the kiai's role is central and significant in encouraging these steps.